Breakdowns - Godfrey Keller; Sven Rady (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
We study a continuous-time game of strategic experimentation in which the players try to assess the failure rate of some new equipment or technology. Breakdowns occur at the jump times of a Poisson process whose unknown intensity is either high or low. In marked contrast to existing models, we find that the cooperative value function does not exhibit smooth pasting at the efficient cut-off belief. This finding extends to the boundaries between continuation and stopping regions in Markov perfect equilibria. We characterize the unique symmetric equilibrium, construct a class of asymmetric equilibria, and elucidate the impact of bad versus good Poisson news on equilibrium outcomes.
urn:nbn:de:bvb:19-epub-14316-0
Keywords: C73; D83; O32; 330; Strategic Experimentation; Two-Armed Bandit; Bayesian Learning; Poisson Process; Piecewise Deterministic Process; Markov Perfect Equilibrium; Differential-Difference Equation; Smooth Pasting; Continuous Pasting